Device-to-device-based proximity service : architecture, issues, and applications /: architecture, issues, and applications. (2017) - (Computer scientist), Wang, Yufeng; Vasilakos, Athanasios; Jin, Q (Qun), 1962-; Zhu, Hongbo
No abstract available